Comprehensive Analysis of Coefficient of Performance (COP) Calculation in Peltier Refrigeration Systems - R. D. Issafira; W. Saputro (BIOMEJ, 2023)
This study delves into the intricate domain of Peltier refrigeration systems, focusing on the crucial parameter of Coefficient of Performance (COP) as a key metric for system efficiency. Peltier devices, known for their solid-state thermoelectric cooling capabilities, have gained prominence in various applications, including electronics cooling, medical devices, and space exploration. The research encompasses a comprehensive review of existing COP calculation methodologies, considering the unique characteristics and operational principles of Peltier modules. Various factors influencing COP in Pertier refrigeration, such as temperature differentials, electrical input power, and thermal resistances, are analysed in detail. Additionally, the impact of material properties, design considerations, and environmental conditions on COP is explored. Furthermore, the research addresses challenges and opportunities in optimizing COP for Pertier refrigeration, considering the trade-offs between efficiency, cost, and practical implementation. Insights from this study aim to contribute to the ongoing efforts in enhancing the sustainability and effectiveness of Peltier refrigeration technologies across various industries.